Photon-Induced Photo-Acoustic Streaming vs. Shock Wave-Enhanced Emission Photo-Acoustic Streaming-The Effect of Three Final Irrigation Protocols on the Bond Strength of an Individually Formed Fiber Post - Cassandra Lupita; Daliana Emanuela Bojoga; Alessandro Del Vecchio; Dan Ioan Stoia; Ion Grozav; Mariana Ioana Miron; Darinca Carmen Todea (MDPI AG, 2024)
(1) Background: This study aimed to evaluate how laser-activated irrigation (LAI) influences the retention of a fiber post when used before an endodontic filling, as well as after post space preparation. (2) Materials and Methods: Sixty freshly extracted human incisors were selected. The teeth were randomly assigned to three groups-CONVENTIONAL (CONV), PIPS or SWEEPS-and treated endodontically. Each group received irrigation with 1 × 5 mL EDTA (17%) and 3 × 5 mL NaOCl (5.25%). In the first group, the irrigants were not activated, while in the second and third group, LAI was adopted using PIPS and SWEEPS protocols (Lightwalker from Fotona, Ljubliana, Slovenia). After post space preparation, each group received the same irrigation protocol initially established. Sticky posts (everStick Post, GC AUSTRIA GmbH Swiss) were individually adapted to the corresponding post spaces and cemented using dual cure resin cement (Gradia Core, GC Austria GmbH Swiss). All specimens were vertically embedded into self-curing acrylate (Duracryl plus, Spofa Dent, Europe), and each was sectioned into three segments of type A and type B samples for debonding through push-out and pull-out tests. The results were statistically analyzed. (3) Results: The pull-out test showed the superiority of the SWEEPS group, with a mean fracture force of 133.0 ± 50.7 N, followed by the PIPS group, with 102 N, with a lower standard deviation of ± 34.5 N. The CONV group registered the lowest fracture force. Concerning the push-out test, the SWEEPS group showed superior shear stress in comparison to the other two groups (13.45 ± 4.29 MPa); the CONV group was inferior, with shear tension values of 8.31 ± 4.67 MPa. (4) Conclusions: It can be stated that the SWEEPS and PIPS protocols resulted in considerably higher fiber post retention than the conventional method, whereas the SWEEPS protocol was superior to the PIPS protocol.